Selective phytochemicals targeting pancreatic stellate cells as new anti-fibrotic agents for chronic pancreatitis and pancreatic cancer - Puvanesswaray Ramakrishnan; Wei Mee Loh; Subash C.B. Gopinath; Srinivasa Reddy Bonam; Ismail M. Fareez; Rhanye Mac Guad; Maw Shin Sim; Yuan Seng Wu (Elsevier, 2020)
Activated pancreatic stellate cells (PSCs) have been widely accepted as a key precursor of excessive pancreatic fibrosis, which is a crucial hallmark of chronic pancreatitis (CP) and its formidable associated disease, pancreatic cancer (PC). Hence, anti-fibrotic therapy has been identified as a novel therapeutic strategy for treating CP and PC by targeting PSCs. Most of the anti-fibrotic agents have been limited to phase I/II clinical trials involving vitamin analogs, which are abundant in medicinal plants and have proved to be promising for clinical application. The use of phytomedicines, as new anti-fibrotic agents, has been applied to a variety of complementary and alternative approaches. The aim of this review was to present a focused update on the selective new potential anti-fibrotic agents, including curcumin, resveratrol, rhein, emodin, green tea catechin derivatives, metformin, eruberin A, and ellagic acid, in combating PSC in CP and PC models. It aimed to describe the mechanism(s) of the phytochemicals used, either alone or in combination, and the associated molecular targets. Most of them were tested in PC models with similar mechanism of actions, and curcumin was tested intensively. Future research may explore the issues of bioavailability, drug design, and nano-formulation, in order to achieve successful clinical outcomes with promising activity and tolerability. Key words: Pancreatic stellate cells, Anti-fibrotic, Chronic pancreatitis, Pancreatic cancer, Phytochemicals, Curcumin, Resverastrol, Rhein, Emodin, Green tea catechin